Legitimacy Deficits of International Organizations: design, drift, and decoupling at the UN Security Council - Matthew D. Stephen (Cambridge Review of International Affairs, 2018)
Despite ubiquitous calls for their reform, international organizations (IOs) often suffer from legitimacy deficits. What explains the emergence of legitimacy deficits and what effects do they produce? This article discusses the gradual emergence of legitimacy deficits through the concept of legitimacy drift. Legitimacy drift occurs when an organization loses legitimacy by failing to adapt itself to a changing environment. It identifies three sources of legitimacy drift: failure to live up to pre-existing standards (broken promises), changes in the standards of legitimacy by which organizations are assessed (shifting standards), and changes in an organization's relevant public (audience shift). Legitimacy deficits typically prompt organizational responses. These include attempts at re-legitimation through institutional reform and operational adaptation, but also other `coping mechanisms' such as promises of reform, the logic of confidence, and decoupling. Coping mechanisms are especially important where reform is blocked. This model is illustrated by the history of the United Nations Security Council, one of the oldest and most powerful IOs. A conclusion calls for bridging historical and sociological institutionalism to better understand IO legitimacy in time.
Keywords: 330